Food consumption, body mass index and risk for oral health in adolescents - Reis Santos, Margarida; Bica, Isabel; Cunha, Madalena; Costa, José; Costa, Patrícia; Bica, Alexandra (Elsevier, 2014)
Objective: The food intake has great in􀃁 uence on the oral health of adolescents, being relevant to analyze the type of food consumed by adolescents and their relationship with the DMFT index (decayed, missing and 􀃀 lled), the plaque index (PI) and the body mass index (BMI). Design: Epidemiological study conducted in public schools of the 3rd cycle of basic education, central Portugal. Instruments: The sociodemographic and dietary habits and frequency characterization was obtained through a self-administered questionnaire completed by adolescents and validated for the population under study. The DMFT index was evaluated according to WHO criteria, oral hygiene was evaluated based on the plaque index and BMI through weight and height in adolescents. Participants: Random sample by clusters (schools) with 661 adolescents, 84.1% female and 15.9% male. Results: Adolescents with mean age 13.22 years (± 1.139). The mean DMFT was 2.23 (± 2.484), the prevalence of PI was 96.4%, and ≥ 5 BMI <85. Adolescents with a higher DMFT index consume more cariogenic foods (r = 0.160; P = .000). Adolescents with a higher BMI consume less cariogenic foods (r = –0.1343; P = .001). The value of t reveals that the consumption of cariogenic foods explains 1.8% of the variance of the BMI and 2.6% DMFT. Conclusion: The cariogenic foods are presented as a risk factor for dental caries. The results suggest that it is important to develop up actions for health education.
Keywords: Adolescents; Diet; Oral health